Pelvic Actinomycosis: a report of two cases with different presentations - Teoh, Soo Huat; Mohd Sopian, Mastura; Draman, Nani; Devaraj, Navin Kumar (Basement Barkat Center, 2020)
Actinomycosisisa type of bacterial infection which manifests in a subacute and chronic manner. It is characterized by a contiguous spread with suppuration and granulomatous inflammation. Actinomycesis a normal flora inhabiting the oral cavity, gastrointestinal and urogenital tract. Thecommonesttype of infection is the cervico facial followed by abdominal and thoracic type. Pelvic actinomycosisis a subtype of abdominal actinomycosis and it is commonly associated with intrauterine contraception device (IUCD) use. The most challenging aspect in management of actinomycosis is to reach the diagnosis early. In cases diagnosed early, removal of IUCD with antibiotic treatment may lead to complete remission averting operative measure and its’ complications. We reporttwo cases of pelvic actinomycosis with different presentations. The first case was diagnosed after patient was operated for suspected gynaecological malignancy while the second case was diagnosed with Papanicolaou smear from routine cervical cancer screening.